Kajian Semiotik E-Poster Peringatan Hari Buku Sedunia Perpustakaan Nasional RI di Instagram - Bima Bijak Prasetyo; Laksmi Laksmi (Pustakaloka, 2020)
The e-poster is used by the National Library of Indonesia in the context of promoting libraries and a culture of reading fondness, in order to realize a lifelong learning community. The purpose of this study was to study the meaning of one of the 2020 World Book Day commemoration e-posters. This research uses the Charles Sanders Peirce Semiotics analysis to find out the meaning contained in the e-poster. The meaning is done by Barthes Semiotic Theory which is the significance of two hangovers. The sign is seen from the two elements of e-poster namely Visual Elements and Text Elements, then analyzed by looking at objects from the aspects of denotation, connotation and myth. The process of analysis obtains meaning obtained from the point of view interpretation (interpreter). With the following results, the e-poster approves the National Book Day of the Republic of Indonesia National 2020 which is displayed on the Instagram account of the national library of the Republic of Indonesia (National Library of the Republic of Indonesia, 2020) which has represented the national promotion library with its function as an institution responsible for encouraging Indonesian people to spend their lives, mandated in Act 43 of 2007 concerning libraries in article 21 paragraph 3